Pelatihan Membuat Bahan Ajar Mata Pelajaran Bahasa Indonesia di MI Muhammadiyah Dukuhturi Bumiayu - Helmi Seftiani; Lutfi Eskawati; Melisa Delia Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This training has several goals, namely to open insights, and observers ofIndonesian teachers about gender equality in everyday life, giving insight to analyzethe value of inequality/ gender equality, and compile teaching materials Indonesian perspective of gender equality. Implementation of this training method is applied intwo stages: the preparation stage and implementation stage. Preparation stageincludes internal coordination (: preparatory concepts, preparation of materials) andthe coordination of external (: contacting a speaker, contact the PDM Bumiayu,Bumiayu Dikspora contacted, and invited the school). Implementation stage is thestage of core training employed by interactive lectures, questions and answers, andtutorials. Training lasted for one day and 13 participants teachers. Based on analysis of implementation of teacher understand thepreparation of teaching materials Indonesian gender perspective. This is evident fromthe responses of the material, examples, and instructional materials containing ilutrasigender inequality